2017
DOI: 10.1093/bioinformatics/btx194
|View full text |Cite
|
Sign up to set email alerts
|

SCODE: an efficient regulatory network inference algorithm from single-cell RNA-Seq during differentiation

Abstract: MotivationThe analysis of RNA-Seq data from individual differentiating cells enables us to reconstruct the differentiation process and the degree of differentiation (in pseudo-time) of each cell. Such analyses can reveal detailed expression dynamics and functional relationships for differentiation. To further elucidate differentiation processes, more insight into gene regulatory networks is required. The pseudo-time can be regarded as time information and, therefore, single-cell RNA-Seq data are time-course da… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
364
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 366 publications
(369 citation statements)
references
References 44 publications
4
364
0
1
Order By: Relevance
“…Inferring gene regulatory relationships is related to the detection of trajectory-associated regulatory genes. Indeed, several single-cell GRN inference methods use trajectories with mechanistic differential equation models (Ocone et al, 2015;Matsumoto et al, 2017).…”
Section: Gene Regulatory Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Inferring gene regulatory relationships is related to the detection of trajectory-associated regulatory genes. Indeed, several single-cell GRN inference methods use trajectories with mechanistic differential equation models (Ocone et al, 2015;Matsumoto et al, 2017).…”
Section: Gene Regulatory Networkmentioning
confidence: 99%
“…While there exist GRN inference methods that were specifically developed for scRNA-seq data (SCONE: Matsumoto et al, 2017;PIDC: Chan et al, 2017;SCENIC: Aibar et al, 2017), a recent comparison has shown both bulk and single-cell methods to perform poorly on these data (Chen & Mar, 2018). GRN inference methods may still offer valuable insights to identify causal regulators of biological processes, yet we recommend that these methods be used with care.…”
Section: Gene Regulatory Networkmentioning
confidence: 99%
“…For this reason, most algorithms require the user to provide a starting position, for example, if the dynamic process involves differentiation, a cell at a pluripotent stage would be chosen as a starting point. Other approaches used for finding such curve are Gaussian Processes and Differential Equations (21)(22)(23).…”
Section: Ti Frameworkmentioning
confidence: 99%
“…As was discussed in the section 'Approaches modelling gradual transitions', cells can be ordered along developmental trajectories. Some network inference methods can include the information from these inferred trajectories to reconstruct dynamic regulatory networks (AR1MA1 [117], SCODE [118]). Another source of external information could come from perturbational studies, in which genes are knocked out and the consequences on the transcriptome can be observed [21].…”
Section: Network Inferencementioning
confidence: 99%